Kebijakan Keamanan Energi Indoneia dalam Pemenuhan Energi Listrik melalui Kerjasama ASEAN Power Grid - Maida Safitri; Khairur Rizki; Zulkarnain Zulkarnain (The Department of International Relations Universitas Mataram, 2021)
This paper aims to determine the urgency and opportunities for cooperation formed by ASEAN member countries. More focus aims to find out the benefits of the cooperation ASEAN Power Grid for Indonesia and analysis energy security policies of Indonesia in meeting the needs of electrical energy with Indonesia. In this implementation, APG has 16 major projects spread across Southeast Asia and 5 of them are located in Indonesia, namely: North Sumatra, Riau, Batam, West Kalimantan, North Kalimantan. Especially for Indonesia represented by PT. PLN Persero as one of the holders of authority in every infrastructure project for the construction of electrical energy networks in Indonesia. In line with the national energy security policy, Indonesia is orienting energy production which initially only focused on fulfilling the export market, leading to the fulfillment of domestic consumption. With the result that the policy to achieve energy security in Indonesia specifically follows the grand framework of the ASEAN Power Grid in accordance with the arguments and principles of cooperation ASEAN Power Grid, where this is realized through the agenda of building electricity infrastructure networks, especially in five regions of Indonesia. Keywords: ASEAN Power Grid , Fulfillment Of Electrical Energy, Infrastructure Development